2009
DOI: 10.1111/j.1540-4609.2009.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaring Them into Learning!? Using a Snake Screen to Enhance the Knowledge Transfer Effectiveness of a Web Interface

Abstract: It seems that surprise events have the potential to turn short-term memories into longterm memories, an unusual phenomenon that may have limited but interesting applications in learning tasks. This surprise-enhanced cognition phenomenon is theoretically modeled based on the notion that many human mental traits have evolved through natural selection; a mathematical analysis building on Price's covariance theorem is employed in this modeling effort. Additionally, the phenomenon is discussed in the context of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…This is likely due to the shocking effects of the more disturbing information on working memory. It has been shown that a shocking event can increase the memory of what was happening just before or after the event (Kock, Chatelain-Jardón, & Carmona, 2009). The pleasing distraction of the comedy video had a less adverse impact on the primary learning activity, but was itself also less memorable than was the news video.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the shocking effects of the more disturbing information on working memory. It has been shown that a shocking event can increase the memory of what was happening just before or after the event (Kock, Chatelain-Jardón, & Carmona, 2009). The pleasing distraction of the comedy video had a less adverse impact on the primary learning activity, but was itself also less memorable than was the news video.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of ICT in its role as an organizational learning enabler Real et al, (2006), it is of crucial significance to enhance the knowledge communication effectiveness/ memorization created/communicated throughout the human computer interface. Previous studies by Kock et al, ( , 2008aKock et al, ( , 2009 and Chatelain et al, (2016) have successfully proven that the incorporation of web-simulated threats enhance knowledge communication effectiveness; however, they fail to recognize that the strength of the negative stimulus presented in the human computer interface directly impacts the level of enhanced knowledge communication effectiveness shown by the subjects.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In like manner, brain mechanisms seem to be rooted at the core of psychology; as Buss (1995) mentions "all psychological theories imply evolved mechanisms" (p. 1) and even though, why or how these brain mechanisms work goes beyond the realm of this research; what is important to emphasize is that "once those mechanisms are in place, they can be activated or executed in ways that may … lead to fitness in current environments" (Buss, 1995, p.10). The studies by Kock et al, ( , 2008aKock et al, ( , 2009 and Chatelain et al, (2016) have used evolutionaryand technology-related web-simulated negative stimulus (threats) to activate the automatic brain mechanisms of surprise. Please note that the surprise model explains how this mechanism has been frequently linked to enhanced memorization capacity.…”
Section: Psychology Brain Mechanisms and The Surprise Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In effect, it appears that surprises "short-circuit" the memory storage process, transferring short-term memories of events directly preceding and following the surprise instantly into long-term memory (Kock, Chatelain-Jardon, & Carmona, 2009, p. 360). Kock et al (2009) investigated how unexpected stimuli impact learning. University students viewed six short, web-based learning modules.…”
Section: Unexpectedmentioning
confidence: 99%